Novel Recycled Triboelectric Nanogenerator Based on Polymer‐Coated Trash Soda Can for Clean Energy Harvesting. (20th August 2021) - Chougale, Mahesh Y.; Saqib, Qazi Muhammad; Khan, Muhammad Umair; Shaukat, Rayyan Ali; Kim, Jungmin; Bae, Jinho
Abstract: Researchers are striving to find the best possible ways to decompose or recycle generated waste to create a pollution‐free environment. Besides the problem of waste pollution, efficient energy generation is another challenging issue across the world. To counter both these problems in a single shot, a unique strategy of reusing and recycling trash soda cans and disposable plastic cups in a simple function change (Funchange) triboelectric nanogenerator (TENG) with a surplus advantage of no chemical processing is presented. The Funchange TENG device presents an excellent output performance with an open circuit voltage, short circuit current, and instantaneous power of 519 V, 82 µA, and 12.25 mW, correspondingly. Further, the fabricated nanogenerator exhibits excellent stability for about 72 000 cycles. This approach of applying trash materials for ultrarobust, high‐performance TENG will pave the path toward sustainable, facile, clean, and environmentally friendly energy scavenging. Abstract : This paper proposes changing the function of trash aluminum soda cans and plastic cups into triboelectric nanogenerators (TENG) to decrease pollution and generate efficient energy without any chemical processing. Applying the trash materials for TENG provides a path toward environmentally friendly efficient energy harvesting.